2022
DOI: 10.1007/s00464-021-08935-8
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the 2020 Fellowship Council application and match process and the impact of COVID-19

Abstract: Background The interview process represents a necessary but potentially resource intensive process from applicant and program perspectives. This study aimed to identify opinions of the 2020 Fellowship Council (FC) application and match process and in-cycle transition to virtual interviews due to the COVID-19 pandemic. Methods Surveys were developed to assess the interview process and were distributed by the FC to all applicants and fellowship programs. Completion was vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In some programs, this time reduction was partially offset by offering more interviews. However, when comparing total person hours (days  faculty  hours), the requirements for VIs were less than for IPIs (Rosenbluth et al 2022). PDs reported that faculty were more likely to participate in VIs due to the reduced time commitment, the ability to participate from anywhere, and the possibility of continuing some clinical duties (Simmons et al 2022).…”
Section: Cost and Time Savings With Virtual Interviewsmentioning
confidence: 99%
“…In some programs, this time reduction was partially offset by offering more interviews. However, when comparing total person hours (days  faculty  hours), the requirements for VIs were less than for IPIs (Rosenbluth et al 2022). PDs reported that faculty were more likely to participate in VIs due to the reduced time commitment, the ability to participate from anywhere, and the possibility of continuing some clinical duties (Simmons et al 2022).…”
Section: Cost and Time Savings With Virtual Interviewsmentioning
confidence: 99%
“…Studies in other subspecialties have concluded that virtual interviews for fellowship programs should be offered in the future, 13,14,18 although some suggest that virtual interviews should be offered in combination with in-person interviews. [14][15][16] Interestingly, a previous study found that a half of interviewers would negatively view fellowship applicants who chose to interview virtually if an in-person interview were offered. 11 This is a concern shared by fellowship applicants, with one study indicating that 97% of applicants would worry that choosing a virtual interview over an in-person one would convey less interest to a program.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies of fellowship applicants have also identified cost savings and less time away from clinical duties as top benefits of virtual interviews. [15][16][17] In addition, applicants in 2020 said they felt that the length of the interviews was shorter than those in 2019. The shorter virtual interview day may help facilitate scheduling multiple interviews at a time and thus improve efficiency and accessibility, which was deemed a major advantage by candidates.…”
Section: Discussionmentioning
confidence: 99%